Sentiment Analysis as a Tool for Optimizing Educational Strategies and Business Communication - Carina Brânzilă (Linguaculture)
This paper explores the complex role of sentiment analysis, a natural language processing (NLP) technique, in various areas, with a particular focus on its application in education and business English learning and communication. Sentiment analysis, which involves extracting and classifying sentiments from text data, is increasingly used worldwide to look into public opinion, customer feedback, and market trends across industries. The paper highlights the potential of sentiment analysis in improving education. Specifically, it examines the integration of sentiment analysis into business English lessons at tertiary level, suggesting two lesson plans designed to equip students with practical skills in employing sentiment data for effective communication. The challenges of implementing such lesson plans are also discussed, alongside some broader implications of sentiment analysis in educational contexts.